Synthesis of 2-[2-(4-Substituted-1,3,5-triazin-2-loxy)phenyl]-3,3-dimethoxypropanoate - Luo, Juan; Yang, Xiu; Wang, Yu-Liang; Wang, Yu-Zhong (Asian Journal of Chemistry, 2015)
In this article, the synthesis of a series of novel compounds, methyl 2-[2-(4-substituted-1,3,5-triazin-2-yloxy)phenyl]-3,3-dimethoxy-propanoate is reported. 4,6-Dichloro-N,N-diethyl-1,3,5-triazin-2-amine reacted with methyl 2-(2-hydroxyphenyl)-3,3-dimethoxypropanoate to give methyl 2-[2-{4-chloro-6- (diethylamino)-1,3,5-triazin-2-yloxy}phenyl]-3,3-dimethoxypropanoate, which then reacted with phenols or thiophenols to give nine novel targets compounds. The structures of target compounds had been characterized by IR, 1H NMR and HRMS.